(untitled) (El-Wahat Journal for Research and Studies, 2025)
A descriptive, analytical and educational article that highlights an aspect of the story’s contribution and its functional role represented by its contribution as an educational tool that can be an effective and influential element in moral guidance. This is done away from the story as a literary art that has its rules, conditions, and manifestations, but our talk is directed to the story with its ancient poetic sides on the one hand, and the Qur’an on the one hand, and what these poetic texts are replete with of events, characters and their nature in this direction and the extent of its impact on behavior Al-Bishri is simulated and influenced by comparison with the stories reported in the Qur’an, whose intention was functional, as the Holy Qur’an itself stated, “And we also narrate to you from the news of the Messengers what we strengthen your heart with.” in it Key words: Old poetry, behavior, modification, setting, story, event, character